2020
DOI: 10.1029/2020gl088227
|View full text |Cite
|
Sign up to set email alerts
|

Ballooning‐Interchange Instability in the Near‐Earth Plasma Sheet and Auroral Beads: Global Magnetospheric Modeling at the Limit of the MHD Approximation

Abstract: Explosive magnetotail activity has long been understood in the context of its auroral manifestations. While global models have been used to interpret and understand many magnetospheric processes, the temporal and spatial scales of some auroral forms have been inaccessible to global modeling creating a gulf between observational and theoretical studies of these phenomena. We present here an important step toward bridging this gulf using a newly developed global magnetosphere‐ionosphere model with resolution cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 54 publications
1
106
0
Order By: Relevance
“…Besides, spatial maps of ionospheric currents (not shown) imply that higher resolutions tend to exhibit stronger and smaller-scale ionospheric current patterns. This is consistent with Sorathia et al (2020) who report that the high-resolution global MHD simulation GAMERA produced localized field-aligned current structures. Nevertheless, many observational studies have shown highly-complex ionospheric current features (Apatenkov et al, 2020) such as vortexes (Belakhovsky et al, 2019;Viljanen et al, 2006;Viljanen, Tanskanen, et al, 2006), which pose significant challenges for modelers.…”
Section: Latitudinal and Regional Variabilitysupporting
confidence: 92%
“…Besides, spatial maps of ionospheric currents (not shown) imply that higher resolutions tend to exhibit stronger and smaller-scale ionospheric current patterns. This is consistent with Sorathia et al (2020) who report that the high-resolution global MHD simulation GAMERA produced localized field-aligned current structures. Nevertheless, many observational studies have shown highly-complex ionospheric current features (Apatenkov et al, 2020) such as vortexes (Belakhovsky et al, 2019;Viljanen et al, 2006;Viljanen, Tanskanen, et al, 2006), which pose significant challenges for modelers.…”
Section: Latitudinal and Regional Variabilitysupporting
confidence: 92%
“…The local B z minimum has been previously studied in the RCM (Yang et al., 2010) and in empirical models (Stephens et al., 2013). Other than the adiabatic earthward convection, an alternative to the adiabatic‐earthward‐convection mechanism is proposed by evacuating the magnetic flux from the tail to the flanks (Gordeev et al., 2017; Hsieh & Otto, 2014; V. A. Sergeev et al., 2018; Sorathia et al., 2020).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Other than the adiabatic earthward convection, an alternative to the adiabatic-earthward-convection mechanism is proposed by evacuating the magnetic flux from the tail to the flanks (Gordeev et al, 2017;Hsieh & Otto, 2014;V. A. Sergeev et al, 2018;Sorathia et al, 2020).…”
Section: Implication For the Current Sheet Instabilitymentioning
confidence: 99%
“…We use this simulation, which is described in more detail in Section 2.1 and by Sorathia et al. (2020), to get a realistic distribution of ionospheric currents and associated magnetic field disturbances in a region that is traversed by a simulated EZIE satellite. (2) Zoomed‐in view of magnetic field and currents in this region.…”
Section: Estimating the Electrojet From Simulated Mesospheric Magnetic Field Measurementsmentioning
confidence: 99%